ANALISIS SALURAN PEMASARAN CABAI MERAH (Capsicum annum L.) DI DESA TUMIJAYA KECAMATAN JAYAPURA KABUPATEN OKU TIMUR - Kristianto, Kristianto (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2024)
Red chili is a horticultural product that is in great demand by the public because it contains nutrients that are beneficial for health. This research aims to analyze marketing channels and calculate marketing margins in Tumijaya Village, Jayapura District, East OKU Regency. Location determination was done deliberately. The research method used in this research is the survey method. The sampling method used was a purposive method, where 30 samples were taken from farmers in Tumijaya Village with land area criteria of 0.25 to 0.5 hectares. The research results show that there are two marketing channels for red chilies in Tumijaya Village, Jayapura District, East OKU Regency, namely marketing channels I and II which are indirect marketing channels. Marketing margin on Channel I is IDR 7,000.00 and on Marketing Channel II is IDR 10,000.00.